Desnudar e desnudar-se para o cuidado: enfermagem, pacientes, nudez e bioética - Silva, Josefa Rita da (2017)
The study had as object the observance of the bioethical principles in a relation of nursing care that requires the patient's denudation and that can be seen as a solidary experience or can be configured as a constraint and a break of autonomy. The main objectives were to analyze and discuss the experience of patients when they are denuded by Nursing professionals regarding the observance of bioethical principles. It is a descriptive qualitative research carried out in general public and philanthropic hospitals with persons hospitalized in medical, surgical, UTI and obstetric centers based on inclusion criteria: be over 18 years old and who have needed nursing care where body's denudation was indispensable; Patients in coma and carrying an endotracheal tube were not included. The project was approved by the Research Ethics Committee of the Federal University of Alagoas, according to appear consubstantiated nº. 1653202 and CAAE n. 56197216.8.0000.5013. Ethical care were taken care of. The information were produced between August 2016 and May 2017, through semi-structured interviews with 28 participants of the 33 patients who were approached, which were transcribed and authorized by the participants. After a thorough reading, three interpretive categories emerged, structured from the concepts of the mainstream bioethics of Tom Beauchamp and James Childress: 1. Ethical posture as a predictor of the denudation experience, made up of two subcategories (I - The Nursing knows, does, and tells what to do. II - The local environment does or does not ethical denudation). 2. The observance of bioethical principles in the act of caring influences the patient's response to denudation, with a subcategory (I - Inform, deceive or consent clarification reveals the bioethical act of denudate). 3. Bioethical interaction leads the patient to re-signify his or her denudation by the nursing professional. The study showed that clarification and information are key points with regard to patient satisfaction criteria, being indispensable for the performance and quality of health services and that acts contrary to the preservation of the particularity of the patient cause the violation of privacy and attempt against your morality. Thus, the results predisposed to warn those responsible for hospital institutions and training entities to introduce discussions about the bioethical principles that guide the work of the nursing professional, so that the observance of these principles helps to enhance a more human space and builds more relationships harmonious.